The geology and geochemistry of mafic and intermediate igneous rocks associated with the Cape granites - Jordaan, L. J.(Lodiwikus Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1990.